2007
DOI: 10.1091/mbc.e06-08-0663
|View full text |Cite
|
Sign up to set email alerts
|

Direct Binding to Rsp5 Mediates Ubiquitin-independent Sorting of Sna3 via the Multivesicular Body Pathway

Abstract: The sorting of most integral membrane proteins into the lumenal vesicles of multivesicular bodies (MVBs) is dependent on the attachment of ubiquitin (Ub) to their cytosolic domains. However, Ub is not required for sorting of Sna3, an MVB vesicle cargo protein in yeast. We show that Sna3 circumvents Ub-mediated recognition by interacting directly with Rsp5, an E3 Ub ligase that catalyzes monoubiquitination of MVB vesicle cargoes. The PPAY motif in the C-terminal cytosolic domain of Sna3 binds the WW domains in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

12
91
4
1

Year Published

2007
2007
2015
2015

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 73 publications
(108 citation statements)
references
References 67 publications
12
91
4
1
Order By: Relevance
“…Along these lines, recent studies show that Sna3 can utilize both ubiquitin-dependent and -independent mechanisms for its MVB targeting. Sna3 ubiquitination is dependent on Rsp5, but the function of Rsp5 is also critical for the MVB sorting of Sna3 independent of cargo ubiquitination (McNatt et al, 2007;Oestreich et al, 2007). Here we found that Ath1 has certain properties that are similar to Sna3.…”
Section: A New Signal For Protein Sorting Into Mvb Internal Vesiclesmentioning
confidence: 51%
See 1 more Smart Citation
“…Along these lines, recent studies show that Sna3 can utilize both ubiquitin-dependent and -independent mechanisms for its MVB targeting. Sna3 ubiquitination is dependent on Rsp5, but the function of Rsp5 is also critical for the MVB sorting of Sna3 independent of cargo ubiquitination (McNatt et al, 2007;Oestreich et al, 2007). Here we found that Ath1 has certain properties that are similar to Sna3.…”
Section: A New Signal For Protein Sorting Into Mvb Internal Vesiclesmentioning
confidence: 51%
“…Recent studies showed that Sna3 is also ubiquitinated; however, without ubiquitination it still can utilize an alternative mechanism, which involves the function of Rsp5, to be sorted into the MVB pathway (McNatt et al, 2007;Oestreich et al, 2007). Here we showed that the acid trehalase, Ath1, had the same transport behavior as Sna3.…”
Section: The Transmembrane Domain Of Ath1 Contains An Mvb Sorting Signalmentioning
confidence: 67%
“…Ste6p, the a-factor transporter, is also multiply ubiquitylated and five acceptor lysine residues are known (Kelm et al, 2004). It has also been demonstrated very convincingly that Rsp5p, the E3 ligase that governs ubiquitylation of numerous transmembrane proteins at the yeast plasma membrane (Dunn and Hicke, 2001a;Dupre et al, 2004), is able to generate (Lys63-linked) polyubiquitin chains in a robust fashion (Kee et al, 2006;McNatt et al, 2007;Oestreich et al, 2007). This clearly raises the possibility that oligoubiquitin may be the predominant endocytic sorting signal in yeast.…”
Section: Monoubiquitin Versus Polyubiquitin As An Internalization Signalmentioning
confidence: 97%
“…Liquid cultures (100 ml) of BL21(DE3) transformed with Vps2, Vps20-HA, His 6 -Vps24, and Snf7 expression plasmids were grown and lysed as described previously (McNatt et al, 2007). Lysates were clarified of cell debris by centrifugation at 100,000 g for 30 min at 4˚C.…”
Section: Immunoprecipitations and Western Blottingmentioning
confidence: 99%